Finite Element Analysis on Load-Settlement Behavior of Axially Loaded Pile on Sand - Gupta, Sunil Kumar; Dahal, Bhim Kumar (Journal of Engineering Technology and Planning, 2023)
The analysis of geoengineering problems using various constitutive models necessitates substantial field and laboratory research, which entails a significant investment of time and money. As a result, the application of Finite Element Analysis in geoengineering projects is limited. This research focuses on numerically examining the behavior of a pile in a sandy soil layer. The study employs different relationships to estimate soil parameters from standard penetration tests and simple lab tests. These derived parameters, required for the Mohr-Coulomb & Hardening Soil constitutive model and the linear elastic model of the pile, are implemented in the PLAXIS 3D software. This software is used to simulate the settlement of the pile in sandy soil incorporating factors like mesh density and soil-pile interaction. The results of the study reveal that employing a finer mesh size leads to more precise results. Additionally, an interface strength of 67% proves to be more accurate for this study. Furthermore, the correlation introduced by Papadopoulos (1982) exhibits a close relation with field settlement values. In contrast, other correlations either overestimate or underestimate the results. Moreover, the study conclude that Mohr-Coulomb constitutive model satisfactorily predicts the behavior of the pile for the study area.